The Effects of Surfactant on Combustion Characteristics of Emulsified Diesel Fuel - Ismail, Muhammad Iskandar (Universiti Teknologi Petronas, 2013)
Introduction of water into diesel mixture could be used as an alternative fuels to replace natural hydrocarbon resources that are nearly depleted. The emulsified diesel fuel is defined as emulsions of water in diesel fuel, mixed with a surfactant formulation. This emulsified fuel will be a new solution to the pollution and environmental problems. Problem arises when this emulsion tend to demulsify itself over time. In order to get a good and stabilised emulsion, a correct mixture of water and diesel fuel must be produced. Water in Diesel Emulsion (WiDE) is produced with proportion of 5% water content. The emulsions created will be tested for its stability and property compositions such as Carbon, Hydrogen and Nitrogen content, flame point and molecule composition. As the result, Oxygen content in emulsified diesel fuel is more than ordinary diesel fuel and this clearly shown that the emulsion can provide better combustion. Mixing speed provides more stabilised emulsion as compared to mixing time. Therefore, it is useful to apply mixing speed when preparing emulsified diesel fuel.